Nissan v. Nissan [trademark dispute]. - Cass, S.
Is a trademark dispute a case of David v. Goliath or a corporation fending off a greedy opportunist? This paper discusses the case of Uzi Nissan, who is locked in a multimillion-dollar legal battle over whether or not his use of the nissan.com Internet domain name infringes upon Japan's Nissan Motor Co.'s trademark. At the heart of the matter is the impact of the global Internet on trademark law, which traditionally has been strongly influenced by geographic considerations. The paper discusses the background to the case from both sides and the issues involved.
Keywords: Nissan Motor Company trademark; Uzi Nissan; Global Internet; Nissan.com Internet domain name; Trademark dispute; Trademark law